Desenvolvimento de pães por fermentação natural isentos de glúten com sorgo e subprodutos de maçã e palmito pupunha - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The increase in the population that cannot or chooses not to consume gluten signals the importance of gluten-free bread alternatives. Most of the options available on the market are poor in nutrients and expensive. Research to develop more nutritious and economical bread formulations is essential. Sorghum is a promising option due to its high content of starch (80%), proteins, minerals and phenolic compounds, and its cultivation is expanding in Brazil. The nutritional enrichment of formulations can be achieved at lower costs by using agro-industrial by-products, as many are sources of dietary fiber and bioactive compounds that are important for healthier diets. This study investigated flours produced from the by-products of processing peach palm and apple juice for gluten-free bread formulations. Sourdough, known to increase nutritional value, improve texture, digestibility and extend the shelf life of breads without the use of additives, was used. The by-product flours investigated showed a high fiber content, with peach palm with 49.97 g100g-1 and apple with 37.05 g.100 g-1 . Apple by-product flour had the highest content of phenolic compounds at 20.21 mg acid galic equivalent (EAG).g -1 , while sorghum flour stood out for its antioxidant activity at 1.84 mg Trolox equivalent (ET).g-1 by DPPH and 3.07 mg ET.g-1 by FRAP. Sourdough was produced using rice flour, which proved to be more suitable than sorghum or a mixture of rice and sorghum, based on the monitoring of pH, acidity and fermentation capacity. Two formulations with different proportions of sorghum (50% and 60%) and peach palm and apple by-products were compared in terms of proximal composition, antioxidant activity and phenolic compounds. The formulations had a high fiber content (>7g.100g-1 ) and low energy content (average of 229 kcal.100g-1 ) compared to commercial breads (average of 450 kcal.100g-1 ). The formulation with 60% sorghum was chosen for comparison between sourdough bread (SB) and commercial biological yeast bread (FB) because it was more interesting from the nutritional point of view. The formulation with 60% sorghum had the highest antioxidant activity and was chosen for comparison between sourdough bread (SB) and yeast fermented bread (YB). Color, water activity (Aw), acidity, pH, texture, specific volume, expansion index, digestibility, microbiological and sensory analyses were carried out. NF stood out significantly in terms of specific volume, with 3.25 cm3.g-1 for NF and 2.46 cm3.g-1 for BF, while the expansion index was 1.10 for NF and 0.83 for BF. The chewiness value was lower for SB at 34.42 N and 38.64 N for YB. Digestibility results proved the contribution of sourdough to improving this parameter, as 74.46% of the total starch value in SB was found to be rapid digestible starch and 29.97% slow digestible starch, while 93.94% in YB was found to be rapid digestible starch and 6.82% slow digestible starch. Although the differences in the averages of the attributes obtained in the sensory analysis by the two fermentation methods were not significant, adjustments to the formulations could improve consumer acceptability.
Keywords: digestibilidade; sustentabilidade; sourdough; fibras alimentares; volume específico; digestibility; sustainability; sourdough; dietary fiber; specific volume; CNPQ::CIENCIAS AGRÁRIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS